Modeling of Unsteady Sheet Cavitation on Marine Propeller Blades - Spyros A. Kinnas; HanSeong Lee; Yin L. Young (International Journal of Rotating Machinery)
Unsteady sheet cavitation is very common on marine propulsor blades. The authors summarize a lifting-surface and a surface-panel model to solve for the unsteady cavitating flow around a propeller that is subject to nonaxisymmetric inflow. The time-dependent extent and thickness of the cavity were determined by using an iterative method. The cavity detachment was determined by applying the smooth detachment criterion in an iterative manner. A nonzeroradius developed vortex cavity model was utilized at the tip of the blade, and the trailing wake geometry was determined using a fully unsteady wake-alignment process. Comparisons of predictions by the two models and measurements from several experiments are given.